CARA PRODUKSI PANGAN YANG BAIK UNTUK INDUSTRI RUMAH TANGGA (CPPB-IRT) PERUSAHAAN TAHU PUTIH “SL” KABUPATEN SEMARANG TAHUN 2017 - Iik Santi Komala; Laksmi Widajanti; Dina Rahayuning Pangestuti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
A way to good food production for the household industry (CPPB-IRT) is a guide that explains how to produce food to be safe and feasible for consumption. In 2015, the percentage of IRTP that did not meet the conditions increased during the fourth quarter that is 24,28%, 25,33%, 36,64%, dan 36,64%. The presence of formalin and E. coli is still found in the IRTP product under study. The purpose of this study is to analyze CPPB-IRT in white tofu company “SL” in district Semarang. The type of this study is observational analytic with cross sectional design. Samples in this research are water of marinade white tofu, white tofu, and company owner. The sample is taken by purposive sampling method. The results of the study show 12 critical irregularities found in components of production equipment, water supply, hygiene and sanitation facilities and activities, health and hygiene of workers, maintenance and hygiene and sanitation programs, storage, process control, food labeling, and employees training. 13 serious irregularities found in components of site and production environment, buildings and facilities, production equipment, hygiene and sanitation facilities and activities, maintenance and hygiene and sanitation programs, process control and supervision by responsible person. 5 major irregularities found in components of building and facilities, hygiene and sanitation facilities and activities, health and hygiene of workers and maintenance and hygiene and sanitation programs. The “SL” company being in level IV of IRTP. The sawdust hazard found in white tofu, the formalin hazard are found in acidic water and white tofu, and the existence of E. coli on the water of marinade white tofu and white tofu are not found. The size of water content in white tofu is 79 %, the size of protein content in white tofu is 42,87 %. The “SL” company has to begin pays attention to food safety products it generates with based on the terms of CPPB-IRT.